The Factors Affecting the Formation of Political Behavior in Iranian Sport Ministry and Federations - Robab Mokhtari; Ali Mohammad Safania; Hossein Poursoltan Zarandi (The Society of Aging and Physical Activity (SAPA), 2018)
Background. When asked about employees' political behavior in the workplace, they often see it as signs of good behavior and see it as an ugly act that achieves personal goals at the expense of others, and May be harmful to the goals of the organization or individuals. Objectives. This study aimed to test a model of factors affecting political behavior in the sports industry. In the study, other objectives such as the moderating role of political skills and will, as well as the mediating role of the perception of organizational politics are discussed. Methods. The sample size of the present research is 705 people which are employees of the Ministry of Sport and federations (of football, volleyball, handball, basketball, weight-lifting, wrestling, taekwondo, veterans and disabled). These were selected by simple random sampling and a questionnaire was used to evaluate the variables under study. Results. The results did not show significant direct relationship between inter-organizational factors and show that perception of organizational politics mediated the relationship between inter-organizational factors and political behavior. The results showed that political skills and will, played the role of the moderator of organizational factors with political behavior. Conclusion. Politics is a fact of life in the organizations. Those who are not able to observe their political behavior cannot understand the fact that organization is a political system. Thus, the organizations should lead to the politicization and managers should make necessary attempts towards reaching organizational goals which is important.